Cu(II) adsorption from aqueous solution using red mud activated by chemical and thermal treatment - da Conceição, Fabiano T. [UNESP]; Pichinelli, Beatriz C. [UNESP]; Silva, Mariana S. G. [UNESP]; Moruzzi, Rodrigo Braga [UNESP]; Menegário, Amauri Antonio [UNESP]; Antunes, Maria Lucia Pereira [UNESP] (Springer Nature, 2016)
Brazil is the third-largest producer of aluminium, with the red mud generated during the extraction of aluminium from bauxite through the Bayer process. The red mud has been studied for use as an adsorbent for removing of elements/compounds from wastewater and/or contaminated soil. However, there are several compounds and treatments that were not tested yet. In this study, the Cu(II) adsorption potential for natural red mud (NRN) and red mud activated by thermal treatment at 400 °C (TRM) and chemical treatment with hydrochloric acid (HCl) at 0.05 mol L−1 (CRM1) and calcium nitrate [Ca(NO3)2] 0.1 mol L−1 (CRM2) was evaluated using adsorption isotherms obtained by the Langmuir and Freundlich models. The NRM and TRM presented Cu(II) adsorptions of ca. 100 % in aqueous solution with lower concentrations of the metal (0.5 and 1.0 mmol 25 mL−1). The Langmuir isotherm was more appropriate to describe the phenomenon of Cu(II) removal using NRM, TRM, CRM1 and CRM2, with the thermally activated red mud presenting the highest adsorption capacity at 2.08 mmol g−1 for Cu(II). Thus, these results indicate that TRM has the potential for use in applications that treat effluents and/or contaminated soil from industrial activity.
Keywords: Aluminium production; Cu(II) adsorption; Isotherms models; Red mud